A Methods study on Philippine Automotive Manufacturing Corporation - Abaloso, Czarina; Castillo, Rafael Jr.; Espiritu, Francis; Conzalez, Francisco; Sacramento, Christine; Villar, Allan (Diliman, Quezon City College of Engineering, 1988)
The group's findings concerning their study of the Philippine Automotive Manufacturing Corporation's Lancer SL production methods are as follows : The existing plant assembly layout is the area that would be in most need of attention if any changes in the flow of work and materials are to be considered. The main reason- unnecessary travel and delays due to the inconvenient location of work stations. The following modifications therefore, are aimed towards the optimal use of time and effort through the minimization of unnecessary transport.1) Short Term Changes/Renovations a) relocation of the crates storage section to an area right beside the unboxing section. This would certainly entail costs but in comparison to the amount of effort and time that would be conserved in implementing such a relocation activity, these could be considered as trivial costs. b) relocation of the paint lab, mixing room and paint office to a site right beside the compressor room. Although it would have a menial effect on the painting process, it would allow maximization of space allotted for the rustproofing and paint repair sections. Units may thus be freely transported to these sections without the obstructions provided by the present location of the paint section. c) relocation of the shower or water test area to a site in between the trim line final assembly and the conditioning area. This provides a smooth flow of assembly, testing and reconditioning operations. 2)Long term changes/renovations a) Planning and reconstruction of an ideal plant layout- one which would permit the smoothest flow of materials and processes to ensure the elimination of unnecessary travel. An example of such a layout would be one that originates from the crates storage and unboxing station on one end of the plant area followed all other stations involved arranged exactly in succession until the unit is finally released to the depot area. Management should expect to incur quite an amount in terms of renovation costs and expenses but such expenses should prove their worth in the future operating years of the company. Again, such a decision for total renovation shall be based on management policies.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis